DAMPAK KEPUASAN KERJA DAN KOMITMEN TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA KARYAWAN USAHA KECIL DAN MENENGAH (UKM) (STUDI KASUS UKM DI LAMONGAN) - Ali Muhajir; Martha Laila Arisandra (LPPM UNISDA, 2018)
The purpose of this study is to analyze the impact of job satisfaction and commitment to OCB on the employees of small and medium enterprises (SMEs). Data were obtained from questionnaires. Population at this penalitian is Employee at CV. Paradila as many as 150 Employees and CV. Stars while samples taken 25% obtained as many as 50 people or respondents. F test results obtained F arithmetic > F table (86.085 > 3.20). This proves that job satisfaction variable and commitment to organizational citizenship behavior (OCB) on employees of small and medium enterprises (SMEs) simultaneously influence while t test results obtained X 1 (job satisfaction) t count> t table (3.321> 1.667) while X2 (commitment) is at t count> t table (4.707> 1.667) so it is concluded that the influence of organizational commitment is more dominant than job satisfaction Organizational Citizenship Behavior (OCB) on SME employees.